2002
DOI: 10.1128/aem.68.5.2278-2284.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Levels of the Eukaryotic Translation Initiation Factor 5A Gene Peak at Early G 1 Phase of the Cell Cycle in the Dinoflagellate Crypthecodinium cohnii

Abstract: A cDNA encoding a eukaryotic translation initiation factor 5A (eIF-5A) homolog in heterotrophic dinoflagellate Crypthecodinium cohnii (CceIF-5A) was isolated through random sequencing of a cDNA library. The predicted amino acid sequence possesses the 12 strictly conserved amino acids around lysine 52 (equivalent to lysine 50 or 51 in other eukaryotes). A single 1.2-kb band was detected in Northern blot analysis. In synchronized C. cohnii cells, the transcript level peaked at early G 1 and decreased dramaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The mechanism of translational regulation in dinoflagellates has been evidenced for awhile (36). Together with tRNA synthetases and ribosomal proteins, ubiquitous eukaryotic initiation, elongation, and release factors were well represented in our data set (Table 3), including elongation factor 3 (EF-3) reported here for the first time in dinoflagellates, and translation initiation factor 5A (eIF-5A), which might also be involved in the G 1 /S transition of the cell cycle (6). These were expressed along with mitochondrial or plastid elongation factors (EF-Tu, EF-Ts, and EF-G).…”
Section: Discussionmentioning
confidence: 88%
“…The mechanism of translational regulation in dinoflagellates has been evidenced for awhile (36). Together with tRNA synthetases and ribosomal proteins, ubiquitous eukaryotic initiation, elongation, and release factors were well represented in our data set (Table 3), including elongation factor 3 (EF-3) reported here for the first time in dinoflagellates, and translation initiation factor 5A (eIF-5A), which might also be involved in the G 1 /S transition of the cell cycle (6). These were expressed along with mitochondrial or plastid elongation factors (EF-Tu, EF-Ts, and EF-G).…”
Section: Discussionmentioning
confidence: 88%
“…For instance, the AteIF5A-2 mutant plant is an extreme dwarf with substantially reduced size and number of all adult organs (Feng et al 2007), and the transgenic plants with constitutive AteIF5A-2 overexpression display phenotypes consistent with precocious cell death ). eIF5A has been implicated in translation elongation, mRNA turnover and decay (Schrader et al 2006;Zuk and Jacobson 1998), cell proliferation (Feng et al 2007;Zanelli and Valentini 2005;Chan et al 2002;Park et al 1993b) and PCD, however, in higher plants, the precise physiological function of eIF5A remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In archaea, bacteria, and eukaryotes, AdoMetS catalyzes the formation of S-adenosylmethionine (SAM) from methionine and ATP, and thereby plays a central role as the methyl donor for various proteins, nucleic acids and polysaccharides, as well as for many of the metabolites that are associated with the primary and secondary metabolism of cells [28,29]. Tabor et al [30] found that AdoMetS was involved in the biosynthesis of the polyamines that are required for cellular proliferation and which may play a role in the rapid growth of bloom-forming dinoflagellates [31]. Recently, Ho et al [32] reported that in the dinoflagellate Crypthecodinium cohnii, the expression of both the transcript and the protein of AdoMetS peaked at the G1 phase during the cell cycle; they also observed that the expression of the AdoMetS protein was high on day 1 of the fast growing log phase.…”
Section: Differential Protein Expression Patterns In a Catenella Durmentioning
confidence: 99%